Preparedness of Lab School Middle School Students Towards Earthquakes for Disaster Risk Reduction - Salmawati, Lusia; Pertiwi, Pertiwi; Syahril, Muhammad Sabri; Satria, Muhammad Aji; Radhiah, Sitti; Rahman, Abd (Media Publikasi Cendekia Indonesia, 2024)
The primary objective of this research is to observe and analyze the preparedness of Labschool Middle School students in Palu City for Disaster Risk Reduction. The population in this study consisted of all students at Palu City Labschool Middle School, using a total sampling technique, resulting in a sample size of 100 students. Data was collected using structured questionnaires that were directly filled out by the students. The questionnaires were designed to cover all aspects of the research variables and provide a comprehensive assessment of the student's preparedness. Data processing in this study utilized a computerized system via MS Excel. Knowledge: 95% of respondents rated their knowledge on the subject as not good. This indicates that the majority of respondents have a poor understanding of the topic. Early Warning System: 57% of respondents rated the early warning system as not good. Resource Mobilization: 73% of respondents rated resource mobilization as not good. This indicates significant issues in resource mobilization, with the majority of respondents feeling that improvements are needed in this area. The findings indicate a significant gap in disaster preparedness among Labschool Middle School students. The majority lack basic knowledge about natural disasters and have minimal exposure to disaster-related training or education. Despite the availability of disaster warning tools in schools, awareness and understanding of their use remain limited. An effective early warning system is crucial for community safety, yet many students exhibit low awareness and preparedness levels